Occupational employment projection to 2016. - Dohm, Arlene; Shniper, Lynn (Monthly Labor Review, 2007)
The article discusses the occupational components of the employment projections for the period 2006-2016 in the U.S. It expects the two largest occupational groups in 2006, professional and related occupations and service occupations, to continue to be the largest in 2016. These two groups are seen to be the fastest growing occupations, at 63% of the total projected growth. On the other hand, the fishing, forestry, and farming occupations and the production occupations, are projected to decline over the 10-year span. The article also examines the most significant source of training by occupation, which reveals that the occupations requiring short-term on-the-job training are expected to be about 30% of all new jobs in the period covered.